Het Mundomotorium van Willem Gleuns en Hendrik Deutgen - van den Broek, Hans; Kamphuis, Ben (Studium, 2017)
The Mundomotorium of Willem Gleuns and Hendrik DeutgenIn 1854 Willem Gleuns Jr (1808-1881), a mathematics and physics teacher from the City of Groningen, and Hendrik Deutgen (1816-1887), a laboratory assistant at Groningen University, applied for a recommendation from the Dutch Minister of the Interior for their ‘Mundomotorium ’, a didactic appliance to be used in astronomy lessons at secondary schools. On behalf of the Dutch Royal Academy of Arts and Sciences, the astronomer Frederik Kaiser, director of the Leiden Observatory, examined the instrument and reported to the minister. In October 1854 the minister informed Gleuns that he saw no reason to recommend their instrument for educational purposes. In January 1855 a critical article on the instrument by Jean A.C. Oudemans, observer at the Leiden Observatory, was published in the journal Vaderlandsche Letteroefeningen. Not until the year 2000 the instrument and the accompanying manual were found in the attic of a secondary school in Hengelo, The Netherlands. So far, this instrument has appeared to be the only surviving Mundomotorium. In this article we introduce the instrument and the men who developed it. We also discuss the views of contemporary scientists on the use of didactic instruments in astronomy lessons in secondary schools, in the middle of the nineteenth century.